Effect of bilingualism on visual tracking attention and resistance to distraction - Janic, Ana (Sci Rep, 2020)
Speaking more than one language has been associated with enhanced cognitive capacities. Here we evaluated whether bilingual individuals have advantages in visual tracking attention. Adult bilingual (n = 35) and monolingual (n = 35) participants were tested in the Multiple Object Tracking task (MOT). In one condition, the MOT was performed by itself establishing the baseline performance of each group, and in the other condition, it was performed while participants counted backward out loud in their mother tongue. At baseline, the average speed tracking threshold of bilinguals was not better than that of the monolinguals. Importantly, for bilinguals, counting backward decreased their threshold by only 15%, but, for monolinguals, it decreased it three times as much. This result suggests that bilingualism confers advantages to visual tracking attention when dual tasking is required, extending the evidence that bilingualism affords cognitive benefits beyond verbal communication.